An emerging role of inflammasomes in spinal cord injury and spinal cord tumor - Chen, Jiansong; Shen, Yiguo; Shao, Xiaobo; Wu, Weiliang (Frontiers in Immunology, 2023)
Spinal cord injury (SCI) and spinal cord tumor are devastating events causing structural and functional impairment of the spinal cord and resulting in high morbidity and mortality; these lead to a psychological burden and financial pressure on the patient. These spinal cord damages likely disrupt sensory, motor, and autonomic functions. Unfortunately, the optimal treatment of and spinal cord tumors is limited, and the molecular mechanisms underlying these disorders are unclear. The role of the inflammasome in neuroinflammation in diverse diseases is becoming increasingly important. The inflammasome is an intracellular multiprotein complex and participates in the activation of caspase-1 and the secretion of pro-inflammatory cytokines such as interleukin (IL)-1β and IL-18. The inflammasome in the spinal cord is involved in the stimulation of immune-inflammatory responses through the release of pro-inflammatory cytokines, thereby mediating further spinal cord damage. In this review, we highlight the role of inflammasomes in SCI and spinal cord tumors. Targeting inflammasomes is a promising therapeutic strategy for the treatment of SCI and spinal cord tumors.